Exploring the Role of Gender Stereotype in Teenage Pregnancy in Nabuti Village, Mukono District - Gloria Mukoda (Uganda Christian University, 2025)
The study looked at how gender stereotypes contribute to teenage pregnancy in Nabuti village, Mukono District. Its main objectives were to explore the common gender stereotypes that have led to teenage pregnancy; to identify how gender norms have contributed to teenage pregnancy; and to identify the special intervention to address gender stereotypes and teenage pregnancy in Nabuti village, Mukono district. The study was conducted utilizing a case study research design that also included qualitative research method to acquire the data through the use of interview guide and Focus group discussion. The interview included three department heads and a sample size of 20 respondents who are teenagers, caregivers, head teachers and stakeholders of Mukono child and youth development center. The study findings highlighted the deeply entrenched gender stereotypes in MCDC that leads to teenage pregnancy. These stereotypes create a negative mindset, forcing teenagers to navigate conflicting expectations and stigmas, limiting their access to support and fair treatment. This results in significant challenges for teenagers in limiting their future desires and aspirations in decision-making positions. Moreover, these stereotypes lead to teenage pregnancy. And negatively impact the teen’s academic progress. Addressing these dangerous stereotypes is essential for promoting gender equality in MCDC and similar organizations. Finally, the study recommended MCDC to take appropriate measures, including regular gender sensitization workshops, mentorship programs, gender-neutral recruitment and promotion policies, safe reporting mechanisms, leadership training, promotion of inclusive leadership, and a commitment to gender equality. Additionally, public awareness campaigns should be initiated to challenge and change gender stereotypes in the broader community. These actions aim to foster a more inclusive and equitable work environment, empower women in leadership, and address the deeply rooted gender stereotypes identified in the study.
Undergraduate